Promoting children's learning and development in conflict-affected countries: Testing change process in the Democratic Republic of the Congo. (21st November 2016) - Aber, J. Lawrence; Tubbs, Carly; Torrente, Catalina; Halpin, Peter F.; Johnston, Brian; Starkey, Leighann; Shivshanker, Anjuli; Annan, Jeannie; Seidman, Edward; Wolf, Sharon
Abstract: Improving children's learning and development in conflict-affected countries is critically important for breaking the intergenerational transmission of violence and poverty. Yet there is currently a stunning lack of rigorous evidence as to whether and how programs to improve learning and development in conflict-affected countries actually work to bolster children's academic learning and socioemotional development. This study tests a theory of change derived from the fields of developmental psychopathology and social ecology about how a school-based universal socioemotional learning program, the International Rescue Committee's Learning to Read in a Healing Classroom (LRHC), impacts children's learning and development. The study was implemented in three conflict-affected provinces of the Democratic Republic of the Congo and employed a cluster-randomized waitlist control design to estimate impact. Using multilevel structural equation modeling techniques, we found support for the central pathways in the LRHC theory of change. Specifically, we found that LRHC differentially impacted dimensions of the quality of the school and classroom environment at the end of the first year of the intervention, and that in turn these dimensions of quality were differentially associated with child academic and socioemotional outcomes. Future implications and directions are discussed.